2016
DOI: 10.1021/acs.jpcb.5b11588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salts on the Partitioning of 5-Hydroxymethylfurfural in Water/MIBK

Abstract: This study investigates the influence of electrolytes on the performance of extracting 5-hydroxymethylfurfural (HMF) from aqueous media using methyl isobutyl ketone (MIBK). For that purpose, liquid-liquid phase equilibria (LLE) of quaternary systems containing HMF, water, MIBK and salts were measured at atmospheric pressure and 298.15 K. The salts under investigation were composed of one of the anions NO(3-), SO4(2-), Cl(-), or CH3COO(-) and of one of the alkali cations Li(+), Na(+), or K(+). On the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 45 publications
4
75
0
Order By: Relevance
“…This behavior is also predicted qualitatively correct with ePC-SAFT; the maximum of K ୌ ୵ predicted with ePC-SAFT is slightly over predicted compared to the experimental data. In a previous work [39] this unexpected behavior was investigated; it was observed that strong cation/anion attractions (the formation of ion pairs) strongly contributes to the salting-out of HMF from the aqueous phase. In contrast, the strongly hydrated Li+ ions in aqueous LiCl solutions were found to cause the salting-in of HMF at high LiCl molalities.…”
Section: Water/1-butanol/hmf/saltmentioning
confidence: 95%
See 2 more Smart Citations
“…This behavior is also predicted qualitatively correct with ePC-SAFT; the maximum of K ୌ ୵ predicted with ePC-SAFT is slightly over predicted compared to the experimental data. In a previous work [39] this unexpected behavior was investigated; it was observed that strong cation/anion attractions (the formation of ion pairs) strongly contributes to the salting-out of HMF from the aqueous phase. In contrast, the strongly hydrated Li+ ions in aqueous LiCl solutions were found to cause the salting-in of HMF at high LiCl molalities.…”
Section: Water/1-butanol/hmf/saltmentioning
confidence: 95%
“…De Hemptinne and Lin correlated mean ionic activity coefficients, osmotic coefficients and solid-liquid equilibria of systems containing electrolytes and neutral components [26]. Further, equations of state based on Statistical Associating Fluid Theory (SAFT) [27] were developed recently to model electrolyte systems [28,29] [39].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…5 An efficient extraction requires an adequate solvent, which should have low miscibility with water and lead to a high partition coefficient for each compound. Recent experimental studies have investigated different solvents for extraction [7][8][9][10] and some authors have suggested that 2-butanol and 2-butanone are effective for HMF, while methyl isobutyl ketone (MIBK) is effective for both HMF and furfural compounds. 5,6,9 Other possibility for identifying efficient solvents for extraction is via computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have investigated different solvents for extraction [7][8][9][10] and some authors have suggested that 2-butanol and 2-butanone are effective for HMF, while methyl isobutyl ketone (MIBK) is effective for both HMF and furfural compounds. 5,6,9 Other possibility for identifying efficient solvents for extraction is via computational methods. Thus, Sandler and co-workers 11 have used the COSMO-SAC method to investigate the ability of several linear and branched alcohols to extract HMF from aqueous solution and have found that the method produces reasonable partition coefficients.…”
Section: Introductionmentioning
confidence: 99%